HISTORICAL MEMORIES OF THE GREAT PATRIOTIC WAR IN NARRATIVE SOURCES - Tetuev, Alim Inzrelovic (History, Archeology and Ethnography of the Caucasus, 2020)
The paper explores the memory of the Great Patriotic War in correspondence, memoirs and literary sources of the front-line soldiers and workers of the home front of Kabardino-Balkaria. The state of historiography and the sources of the subject under study are analyzed, its relevance is substantiated. The study has been conducted mainly with the use of historical-comparative and historical-anthropological methods. The author summarizes experience of party-political and agitation-propaganda work of the Main Political Directorate of the Workers’ and Peasants’ Red Army and local party and Soviet bodies for educating Red Army men and home front workers in the spirit of Soviet patriotism, national unity, hatred towards the German occupiers and faith in victory.A number of letters of front-liners to their family members, workers of the home front, local party and soviet authorities have been discovered and studied; in them, the moral and political state of the soldiers and commanders of the Red Army is revealed. The author highlights characteristic features of the letters’ style, their exceptional reliability and persuasiveness, containing the appeal of a great, mobilizing force.The letters of family, workers of the home front, local party and soviet authorities to the front-line soldiers reported on the labor achievements of factories and collective farms, and assistance to the front have been studied.The analysis of the letters and appeals allow to point out the factors which resulted in the victory of the Soviet people in the Great Patriotic War.The reflection of the war in the literary sources of front-line soldiers, which are dedicated to the people of the front and rear, is considered. They focus on adherence to universal human values, courage, patriotism, unity, and heroism.The analysis of the subject under study revealed that the tasks of rallying and mobilizing all forces to achieve victory were characteristic of the consciousness of front-line soldiers and the rear in an extreme situation.
Keywords: Great Patriotic War; historical memory; letters; appeals; front; rear; front-liners; unity; patriotism; feat.